Evaluation of the benefits, harms and cost‐effectiveness of potential alternatives to iFOBT testing for colorectal cancer screening in Australia. Issue 2 (8th March 2018) - Lew, Jie‐Bin; St. John, D. James B.; Macrae, Finlay A.; Emery, Jon D.; Ee, Hooi C.; Jenkins, Mark A.; He, Emily; Grogan, Paul; Caruana, Michael; Sarfati, Diana; Greuter, Marjolein J.E.; Coupé, Veerle M.H.; et al.
Abstract : The Australian National Bowel Cancer Screening Program (NBCSP) will fully roll‐out 2‐yearly screening using the immunochemical Faecal Occult Blood Testing (iFOBT) in people aged 50 to 74 years by 2020. In this study, we aimed to estimate the comparative health benefits, harms, and cost‐effectiveness of screening with iFOBT, versus other potential alternative or adjunctive technologies. A comprehensive validated microsimulation model, Policy1‐Bowel, was used to simulate a total of 13 screening approaches involving use of iFOBT, colonoscopy, sigmoidoscopy, computed tomographic colonography (CTC), faecal DNA (fDNA) and plasma DNA (pDNA), in people aged 50 to 74 years. All strategies were evaluated in three scenarios: ( i ) perfect adherence, ( ii ) high (but imperfect) adherence, and ( iii ) low adherence. When assuming perfect adherence, the most effective strategies involved using iFOBT (annually, or biennially with/without adjunct sigmoidoscopy either at 50, or at 54, 64 and 74 years for individuals with negative iFOBT), or colonoscopy (10‐yearly, or once‐off at 50 years combined with biennial iFOBT). Colorectal cancer incidence (mortality) reductions for these strategies were 51–67(74–80)% in comparison with no screening; 2‐yearly iFOBT screening ( i.e . the NBCSP) would be associated with reductions of 51(74)%. Only 2‐yearly iFOBT screening was found to be cost‐effective in all scenarios in context of an indicative willingness‐to‐pay threshold of A50, 000/life‐year saved (LYS); this strategy was associated with an incremental cost‐effectiveness ratio of A2, 984/LYS–A5, 981/LYS (depending on adherence). The fully rolled‐out NBCSP is highly cost‐effective, and is also one of the most effective approaches for bowel cancer screening in Australia. Abstract : What's new? The Australian National Bowel Cancer Screening Program (NBCSP) will fully roll out biennial screening using the immunochemical Faecal Occult Blood Test (iFOBT) in people aged 50‐74 years by 2020. This is the first study to perform a comprehensive evaluation of the comparative health benefits, harms, and cost‐effectiveness of iFOBT versus other potential colorectal cancer screening strategies using alternative modalities, including pDNA, fDNA, sigmoidoscopy, CTC and colonoscopy within a nationally‐organised bowel cancer screening program. The findings support the rollout of the NBCSP, which was found to be cost‐effective and associated with a favourable benefits‐to‐harm balance when compared with the other strategies.